Detection of Herpesviruses in Wild Bird Casualties in Slovenia - Žlabravec, Zoran; Slavec, Brigita; Vrezec, Al; Kuhar, Urška; Zorman Rojs, Olga; Golob, Zlatko; Račnik, Jožko (Frontiers in Veterinary Science, 2022)
The complete host range of avian herpesviruses in wild birds is unknown, and information about nucleotide sequences is available only in limited cases. The aim of this study was to detect the presence of herpesviruses in wild birds and to gain more information about their phylogenetic relationship. Oropharyngeal and cloacal swabs from 447 wild birds from 15 different orders presented as wildlife casualties were examined for herpesvirus presence with PCR targeting a fragment of the DNA polymerase gene. Herpesviruses were detected in oropharyngeal and/or cloacal swabs in 34 (7.5%) birds belonging to 11 species from six different avian orders: Accipitriformes, Charadriiformes, Columbiformes, Falconiformes, Passeriformes, and Strigiformes. The results of phylogenetic analysis showed that various herpesviruses sequences are present in the wild bird population. Some herpesviruses are host species–specific, whereas in some cases very similar sequences were detected through different avian orders, which confirms findings that herpesviruses are not always restricted to bird species. It seems that herpesvirus transmission could occur by predation from avian prey, and even by superpredation—for example, large owls, such as the Eurasian eagle owl (Bubo bubo) or Ural owl (Strix uralensis), preying on smaller raptors. This can lead to greater infection exposure and is in line with the fact that raptors were the most infected species group. Nevertheless, the individual or simultaneous detection of herpesviruses in oropharyngeal and cloacal swabs shows that both swab samples should be used for herpesvirus detection in wild birds.